Transforming hydropower: An in-depth systematic review of climate change impacts - Ricky Anak Kemarau; Siti Norliyana Harun; Zulfaqar Sa’adi; Marlia Mohd Hanafiah; Zaini Sakawi; Muhammad Ammar Fakhry Norzin; Wan Shafrina Wan Mohd Jaafar; Stanley Anak Suab; Oliver Valentine Eboy; Khairul Nizam Abdul Maulud (Elsevier, 2025)
Hydropower is a cornerstone of the global renewable energy transition, yet its reliability is increasingly threatened by climate change-induced shifts in hydrological cycles. This systematic review critically examines how climate change affects hydropower sustainability through water availability, streamflow variability, and the frequency of extreme weather events. Guided by the PRISMA framework, 124 peer-reviewed studies were analyzed to explore three core dimensions: global impact patterns, regional vulnerabilities, and adaptation strategies. The central research question addresses how climate and hydrological variability shape the operational and strategic sustainability of global hydropower systems. Results reveal pronounced regional disparities. Arid zones such as Northern Africa and the Mediterranean face substantial reductions in water availability, while high-altitude areas like the Himalayas experience increasing seasonal flow variability. Conversely, regions like Northern Europe may benefit from enhanced precipitation. These dynamics reflect broader climatic trends—rising temperatures, earlier snowmelt, and increased evaporation—that are already reducing hydropower reliability in vulnerable areas. The review identifies promising adaptation pathways. Technological innovations, including AI-driven water management and advanced turbine systems, enhance operational efficiency under uncertain conditions. Additionally, governance strategies such as Integrated Water Resource Management (IWRM) and transboundary agreements offer institutional mechanisms to coordinate water use and mitigate resource conflicts. By synthesizing global trends and region-specific responses, this review offers critical insights to inform climate-resilient hydropower planning, infrastructure investment, and policy development. It underscores the need for interdisciplinary collaboration and forward-looking adaptation to secure hydropower's role in a changing climate.